Influence of internet-media discourse on teachers' tolerance towards third-country nationals - Pičukāne, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The impact of media discourse on the tolerance or intolerance, and other forms of social action is not noticeable in everyday life and difficult to prove, but it accumulates with time into a sizeable effect. Teachers receiving information over public opinion and media discourse, which affects their tolerance or intolerance towards third-country nationals. Media discourse has become the most accessible and often the only source of information on a community and a culture of third-country nationals. Thus, it can be argued that internet media discourse directly influences teacher's tolerance or intolerance towards the target group mentioned above.